(untitled) (Journal of Atomic and Molecular Sciences, 2019)
Electrochemical water splitting has been known as a promising and environmental approach to produce hydrogen by avoiding relying on fossil fuels. Unfortunately, the efficient and large-scale H_2 production is still hindered by the sluggish kinetics of the oxygen evolution reaction (OER) at the anode side of a water electrolyzer. Herein, we report a novel amorphous sulfide doped cobalt oxide (amorphous Co-S-O) nanosphere as an efficient electrocatalyst for OER. The Co-S-O electrode exhibits high HER activity and good stability.